Cytotoxic effects of octenidine mouth rinse on human fibroblasts and epithelial cells – an in vitro study. (2nd July 2016) - Schmidt, J.; Zyba, V.; Jung, K.; Rinke, S.; Haak, R.; Mausberg, R. F.; Ziebolz, D.
Abstract: Objectives : This study compared the cytotoxicity of a new octenidine mouth rinse (MR) against gingival fibroblasts and epithelial cells with different established MRs. Methods : The following MRs were used: Octenidol (OCT), Chlorhexidine 0.2% (CHX), Listerine (LIS), Meridol (MER), Betaisodona (BET); and control (medium only). Human primary gingiva fibroblasts and human primary nasal epithelial cells were cultivated in cell-specific media (2 × 10 5 cells/ml) and treated with MR for 1, 5, and 15 min. Each test was performed 12 times. Metabolism activity was measured using a cytotoxicity assay . A cellometer analyzed cell viability, cell number, and cell diameter. The data were analyzed by two-way analysis of variance with subsequent Dunnett's test and additional t -tests. Results : The cytotoxic effects of all MRs on fibroblasts and epithelial cells compared to the control depended on the contact time ( p < 0.001). OCT and BET showed less influence on cell metabolism in fibroblasts than other MRs. OCT also demonstrated comparable but not significant results in epithelial cells ( p > 0.005). Cell numbers of both cell types at all contact times revealed that OCT showed a less negative effect ( p > 0.005), especially for epithelial cells compared to CHX after 15 min ( p < 0.005). OCT and BET showed the best results for viability in fibroblasts ( p > 0.005), but MER showed less influence than OCT in epithelial cells ( p < 0.005). Conclusions : OCT is a potential alternative to CHX regarding cytotoxicity because of its lower cell-toxic effect against fibroblasts and epithelial cells.